Peran Pemimpin Dalam Memotivasi Keprofesionalisme Pers di Kantor Persatuan Wartawan Indonesia (PWI) Kabupaten Deli - solidaritas Gea (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2021)
The success of an organization either in whole or in various groups in a particular organization depends on the quality of a leader in the organization concerned. Because in an organization the leader has a very dominant role in the success of the organization in carrying out various activities. The formulation of the problem in this study is "Motivation of leaders to press workers in increasing the professionalism of the press in the Indonesian Journalists Association, Deli Serdang Regency". The conclusions obtained from this research are: Leader's motivation to increase the professionalism of the press provides energy that drives all existing potentials, creates high and noble desires, and increases togetherness. Each party works according to established rules or standards with mutual respect, mutual need, mutual understanding, and respect for the rights and obligations of each and the entire operational work process.